Validitas tes tertulis pada model pembelajaran blended learning mata pelajaran IPA di SD - Aliani, Gazella Fitri (ARKA INSTITUTE, 2022)
A written test is a collection of questions given to students to test the level of students' knowledge of the material presented. A suitable subject for written tests is science. Before the written test is held, you must use a learning model that is appropriate to the situation where Covid-19 has hit Indonesia, namely using the Blended Learning learning model. To guarantee the quality of the written test, a special study is needed to assess validity. This research aims to assess aspects of the validity of written tests. This research is a descriptive quantitative research that presents data from validation results and validator suggestions regarding the validity of written tests. The validators consisted of two people, namely one lecturer at PGRI Adi Buana University Surabaya and the other a class V teacher at SDN Pepelegi II Waru. The instrument used is a written test sheet. The results of the analysis of the validation sheet show that in general the written test meets the valid criteria. So it can be concluded that the Blended Learning learning model is suitable for use in the learning process.